ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PENENTUAN UPAH MINIMUM PROVINSI DI PULAU JAWA - Siti Mar'atus Sholekhah (2022)
This research aims to determine the factors that influence the determination of the provincial minimum wage in Java Island in 2011-2020 (by excluding DKI Jakarta). The data used in this study is secondary data obtained through the UPNVJ IE Digital Lab. In processing the results of the research, the data analysis used is a panel data regression analysis method where the method is used to measure the influence of independent variables on dependent variables. The results of the regression analysis of the panel data showed that (1) there was a significant positive influence between gross regional domestic product (GRDP) on the provincial minimum wage (2) there was a significant negative influence on the provincial minimum wage (3) there was no effect of the number of the labor force on the provincial minimum wage.